Odpowiedzi

2010-03-04T20:03:00+01:00
A) 1/3x -2=x+2
1/3x-x=2+2
1/3x-3/3x=4
-2/3x=4 /:(-2/3)
x=6
b) 1-6/7x=4/7
-6/7x=4/7-1
-6/7x=-3/7 /:(-6/7)
x=1/2
c) 6(1/4x-2)=18
1,5x-12=18
1,5x=18+12
1,5x=30 /:1,5
x=20
d) x/6-1/6=1
x/6=1+1/6
x/6=7/6 /×6
x=7
e) -2(2x-1)=x/3
-4x+2=x/3 /×3
-12x+6=x
-12x-x=-6
-13x=-6 /:(-13)
x=6/13
f)2/5(3-x)=-2
6/5-2/5x=-2
-2/5x=-2-6/5
-2/5x=-10/5-6/5
-2/5x=-16/5
x=8
g) 3/4(2-3x)=-6
6/4-9/4x=-6
-6/4x=-6-6/4
-6/4x=-24/4-6/4
-6/4x=-30/4
x=5
h) 1/5(x-3)=9-x
1/5x+x=9+3/5
1/5x+5/5x=40/5+3/5
6/5x=43/5 /:6/5
x=6/43

myśle że jest dobrze ale nie jestem pewna przykładu e) i h)


właśnie e i h jest źle, ale dziękuje za resztę